Assessment of factors and improving cheating behaviors among 2nd year medical laboratory students in Adigrat University, Northern Ethiopia, 2018 - deres, abel; Tadesse Bekele, Senait; Kahsu Abay, Getachew; G/hiwot, Teame (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
Cheating during examination is now day serious problem spatially in Ethiopia where many students sit in one class to exam. When cheating occurs in medical schools, it has serious consequences for human life, social values, and the economy. Even though, cheating on exams has existed in any department, with unknown reason, prevalence of cheater among 2nd year laboratory students were high. So that assessing factors and improving cheating behavior of the students are mandatory to create competitive graduated students. To identify factors and to improve cheating behavior action research study design was conducted among 2nd year medical laboratory student. Criterion sampling technique was used to selects sixteen cheater students among 2nd year laboratory students. To gather necessary data, we used focus group discussions, individual interview, open-ended questionnaire and observation and collected information by using hand writing notes. During exam different cheating methods used by students like using a system of signals, writing on hands, desks and copy the other students answer. While the compelling reasons for cheating were like hard courses, hard exams, time pressure and fear of failure. To improve cheating behavior of the student’s different action strategies were taken like prepared exam by using code, arrangement sitting style during exam and sit with brainy students during class, reading and discussion. Most students were trying to done exam by themselves but their results are not good as previously. So that, we need more future action plan to avoid cheating behavior of the students. During, the next action plan we will be taken the remaining main action strategies and action evaluation we will be expected 50% of participants will be avoided their cheater behavior and done exam independently without forced by the environment.